Influence of Strategic Priorities of SMEs on Their Decision to Adopt ERP - Singh Tomar, Jitendra (International Journal of Scientific Research and Management (IJSRM), 2017)
ERP is a major IT investment for SMEs, which can be considered as a strategic decision. The article tests how strategic priorities of SMEs influence their adoption of an ERP system. An investigation on 203 firms shows that reactivity Stratagem is the only strategic positioning increasing the probability to adopt an ERP. Business strategies focused on the characteristics of the products have no influence. In addition, the investigation confirms that the size, the group membership and the IT maturity of SMEs lever ERP adoption.